STUKTUR KEPEMILIKAN SAHAM TERHADAP KEBIJAKAN HUTANG DAN NILAI PERUSAHAAN SEKTOR PROPERTIES & REAL ESTATE - Kurniawan, Fauzi; Sutanti, Sutanti (Taksasila Edukasi Insani, 2025)
This study aims to analyze the effect of share ownership structure on debt policy and company value in the properties real estate sector listed on the Indonesia stock exchange for the 2019-2023 period. This research design is associative with quantitative type. The data used is secondary data in the form of financial reports published by the Indonesia Stock Exchange. The population used is the properties real estate sector companies listed on the Indonesia Stock Exchange as many as 93 companies, then with a sampling technique using purposive sampling method so as to get a selected sample of 5 companies. The analysis method used is multiple linear regression with panel data. The results of this study indicate that managerial ownership and institutional ownership have a negative and insignificant effect on the debt policy of properties real estate companies. In addition, managerial ownership and institutional ownership have a significant positive effect on the firm value of properties real estate companies. Keywords : ownership structur, debt policy, firm value